2020
DOI: 10.1097/fjc.0000000000000758
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Cannabinoid Receptors Attenuates Endothelin-1–Induced Mitochondrial Dysfunction in Rat Ventricular Myocytes

Abstract: Evidence suggests that the activation of the endocannabinoid system offers cardioprotection. Aberrant energy production by impaired mitochondria purportedly contributes to various aspects of cardiovascular disease. We investigated whether cannabinoid (CB) receptor activation would attenuate mitochondrial dysfunction induced by endothelin-1 (ET1). Acute exposure to ET1 (4 hours) in the presence of palmitate as primary energy substrate induced mitochondrial membrane depolarization and decreased mitochondrial bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 75 publications
(7 reference statements)
4
18
0
Order By: Relevance
“…The present study extends extant evidence indicating possible beneficial effects of ECS activation in the stressed myocardium (Wagner et al, 2001;Lu et al, 2014;Lu et al, 2020). Overall, this study demonstrated three salient findings regarding the cardiac effects of the peripherally restricted, dual CBR agonist CB13 in rats: 1) lack of CB13-dependent chronotropic, dromotropic or hemodynamic effects in the non-paced ex-vivo preparation; 2) an ability of CB13 to antagonize the AERP remodelling induced by acute atrial tachypacing; 3) AMPK activation may contribute to the ability of CB13 to protect against tachypacing-induced atrial remodelling.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The present study extends extant evidence indicating possible beneficial effects of ECS activation in the stressed myocardium (Wagner et al, 2001;Lu et al, 2014;Lu et al, 2020). Overall, this study demonstrated three salient findings regarding the cardiac effects of the peripherally restricted, dual CBR agonist CB13 in rats: 1) lack of CB13-dependent chronotropic, dromotropic or hemodynamic effects in the non-paced ex-vivo preparation; 2) an ability of CB13 to antagonize the AERP remodelling induced by acute atrial tachypacing; 3) AMPK activation may contribute to the ability of CB13 to protect against tachypacing-induced atrial remodelling.…”
Section: Discussionsupporting
confidence: 86%
“…However, CB13 treatment caused a significant upregulation of PGC-1α. We previously speculated that CB13 activates AMPK via CB2R whereas CB1 receptors invoke other signaling pathways (Lu et al, 2020). In addition, Zheng et al demonstrated that JWH-133, a CB2Rselective agonist, adequately activated AMPK to stimulate PGC-1α, without CB1R interaction (Zheng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations